Assessment of trace elements in the long-term banana cultivation field’s soil - Islam, Md Saiful; Islam, Md Towhidul; Ismail, Zulhilmi; Islam, Abu Reza Md Towfiqul; Khan, Rahat; Hasan, Fakhrul; Kabir, Md Humayun; Ezewudo, Bede Izuchukwu; Ibrahim, Khalid A.; Idris, Abubakr M. (Frontiers in Environmental Science, 2023)
This work assesses the contamination of trace elements (Cr, Cu, Ni, As, Zn Cd, Mn, Fe, and Pb) in soil and different tissues of the banana plant (Musa spp.), the ecological risks of trace elements using various indices, and the probable health risks using a chemometric approach. Soil and different banana plant tissues were collected from banana fields around the industrial area of the capital of old Pundranagar (the earliest urban archaeological location), Bangladesh. Samples were digested by acid digestion, and trace elements were measured by inductively coupled plasma spectrophotometer (ICP-MS). The concentrations of Cr, Ni, Cu, As, Cd, Pb, Fe, Mn, and Zn in soil ranged from 1.50–61.7, 2.42–87.4, 2.00–100.8, 0.25–31.2, 0.10–12.7, 0.60–91.8, 11330–23782, 8.69–105.9, and 7.50–125.9 mg/kg, respectively. The mean concentrations of trace elements in four tissues descend in order of roots > leaves > stems > fruits. The abundances of trace elements varied in both soil and plant samples, which apparently occurred due to the variations of soil parent materials and the excessive use of agrochemicals for long-term banana cultivation. The soil exhibited a moderate to high degree of contamination with trace elements, and Cr, Pb, Zn, Cd, and As mainly originated from anthropogenic sources. Both non-cancer and cancer risks were perceived due to Cr and As exposure from the fruit tissue of banana plants in the study area.